2010
DOI: 10.1007/s11670-010-0087-7
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant enzymes and cancer

Abstract: Although oxidation is the most common biological and energy producing reaction, oxidative stress is harmful to cell, because the products of oxidation such as free radicals and peroxides damage the cellular components, causing several diseases. Damage in DNA is responsible for cancer formation and progression. However, several enzymes such as superoxide dismutase, catalase, glutathione peroxidase, glutathione reductase, glutathione S-transferase etc. act as antioxidants to influence oxidative stress. Polymorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(33 citation statements)
references
References 47 publications
2
29
0
2
Order By: Relevance
“…[13,14] Cancer patients show depressed adaptogenic functions in the body, including those of antioxidant protection. [15] We know about an important role of glutathione in antioxidant lung protection. [16] Some papers have shown that GGT-dependent prooxidant reactions are involved in inhibition of cancer cells proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…[13,14] Cancer patients show depressed adaptogenic functions in the body, including those of antioxidant protection. [15] We know about an important role of glutathione in antioxidant lung protection. [16] Some papers have shown that GGT-dependent prooxidant reactions are involved in inhibition of cancer cells proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…The role of MnSOD and its changes in gene expression during tumorigenicity in several cancer cell lines have been areas of intense investigation in the last decades; these studies have been reviewed in recent years [48,49,51]. In human bladder cancer, however, such information is quite limited.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of curcumin on GST expression are complex and may involve competitive enzyme inhibition as well as indirect enzyme induction [25]. Genetic polymorphisms in GST and its altered expression and activity are associated with oxidative DNA damage with subsequent risk of cancer susceptibility [26]. The inducible response of curcumin action biomarker GST is sharper and lasted longer in case of the NCD in comparison to CUR.…”
Section: Discussionmentioning
confidence: 99%